Kegamangan Sistem Perlindungan dan Pengelolaan Lingkungan: Melihat UU Ciptaker dari Perspektif Prinsip Non-Regresi - Wibisana, Andri G. (UI Scholars Hub, 2025)
This article evaluates the Environmental Protection and Management Law (UUPPLH) as amended by the Omnibus Law on Job Creation (UUPPLH-Ciptaker) and its implementing regulations. The evaluation uses the normative framework of the principle of non-regression to assess whether the provisions of the UUPPLH-Ciptaker and its implementing regulations represent a setback compared to the legal conditions prior to the enactment of the Omnibus Law. This paper argues that the changes introduced by the UUPPLH-Ciptaker indicate several regressions in Indonesia’s environmental law, particularly in the following areas: a) the weakening of provisions on Environmental Impact Assessment (AMDAL) and Environmental Management and Monitoring Efforts (UKL-UPL); b) the weakening of public participation in AMDAL-related decision-making; c) the replacement of environmental permits with environmental approvals, which results in uncertainty regarding the nature of this instrument—whether as an object of administrative dispute, supervision, or administrative sanctions such as suspension and revocation; d) setbacks in clarity regarding administrative supervision and sanctions, especially in relation to environmental approvals, technical approvals, and what is referred to as PB-related-to-PL; e) the dismantling of strict liability, particularly through Government Regulation No. 22 of 2021; and f) unnecessary decriminalization and conflicting formulations of criminal provisions. If sustainable development remains a goal of national development, the non-regression principle requires that the UUPPLH be removed from the scope of the Omnibus Law.